ﻋﻮاﻣﻞ اﻟﺘﻔﻮق اﻟﺪراﺳﻲ ﻟﺪى طﻠﺒﺔ اﻟﻤﺮﺣﻠﺔ اﻟﺜﺎﻧﻮﯾﺔ (Journal of the College of Education for Women, 2019)
The research aims to identify the factors of academic excellence among the students of secondary stage , the researchers prepared a questionnaire private factors of academic excellence in Secondary stage students, applied to the sample of students reached (40) students from excelling academically, and revealed the results of the study that the most important factors of academic excellence are (Satisfaction of parents and the Satisfaction of God Almighty was the reason for excellence, to rely on myself and take responsibility to ensure the future was the impetus to excellence,understand the questions test scores befor answering reason to get the highest grades , the importance of science as the virtue of God Almighty and His Messenger ( ) represents a motivation to excel , Review student preparations more than once daily enhances the superiority).